1987
DOI: 10.1007/bf02297325
|View full text |Cite
|
Sign up to set email alerts
|

Development and survival ofhaemonchus contortus larvae on pasture in iraq

Abstract: The survival of Haemonchus contortus infective larvae on pasture and soil was studied over a period of 12 months in the Baghdad area. Infective larvae were found on herbage and soil at all times except in the summer months. During autumn and winter infective larvae in pasture survived for periods of up to 32 weeks. Little larval migration into soil was observed during this study and larvae did not survive for long in the faecal pellets during the summer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
1
4
1
1
Order By: Relevance
“…Thus lack of moisture when the eggs were deposited on the grass plots might have been responsible for the eggs failing to develop to infective larvae. These findings are also in agreement with those of Silverman and Campbell (1959) and Rose (1963) in the United Kingdom, Okon and Enyenihi (1977) in the western region of Nigeria and Altaif and Yakoob (1987) in Iraq. However, in May to October, when larvae were recovered from pasture after one week, rain had fallen within that time.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus lack of moisture when the eggs were deposited on the grass plots might have been responsible for the eggs failing to develop to infective larvae. These findings are also in agreement with those of Silverman and Campbell (1959) and Rose (1963) in the United Kingdom, Okon and Enyenihi (1977) in the western region of Nigeria and Altaif and Yakoob (1987) in Iraq. However, in May to October, when larvae were recovered from pasture after one week, rain had fallen within that time.…”
Section: Discussionsupporting
confidence: 93%
“…At no time during the study did the mean monthly temperature exceed 31°C while the minimum was l5.K. This contrasts with the results from similar studies in the USA (Anderson et al, 1966), Australia (Donald, 1968) and Iraq (Altaif and Yakoob, 1987) which showed that the high temperatures during their summer months are very unsuitable for the development and survival of H. contortus larvae. It also differs from the situation in Southern England where the cold winter climate is not favourable for development (Gibson and Everett, 1976).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…De igual manera, Silva et al (2010) indican que la precipitación favorece la migración larvaria, por lo que a mayor precipitación y humedad, mayor cantidad de larvas en los pastizales. En este sentido, Altaif & Jacobs (1987) y Arece & Rodríguez (2010) en Iraq y Cuba, respectivamente, atribuyen que la dinámica de las L 3 en el pasto se debe a los efectos positivos de las precipitaciones, la temperatura y la radiación solar. La especie H. contortus fue la más abundante, con una presencia de 80% del total de los meses de muestreo, incluyendo períodos de sequía.…”
Section: Discussionunclassified
“…Under favourable warm and humid climates, L3 may survive in pastures up to one year while under cooler climates, L3 survival usually is weeks to a few months (Shakya 2007). An earlier study by Altaif and Yakoob (1987) reported infective larvae in pasture survived up to 32 weeks during autumn and winter. The population of H. contortus increased in response to rainfall and declined when "self-cure" occurred within the period of optimal temperature (Gordon 1948).…”
Section: Seasonal Survival By Haemonchus Contortusmentioning
confidence: 97%